High-quality mesh generation for human hip based on ideal element size: methods and evaluation. (31st October 2017) - Wang, Monan; Gao, Jian; Wang, Xinyu
Abstract: The objective of this work was to obtain high-quality mesh generation results for the human hip. This study adopted an edge-collapse algorithm based on quadric error metrics to simplify the hip model. The adjacent triangular areas and a cost function that considered the mean value of error were introduced to avoid error accumulation and ensure invariant geometric features. Local mesh refinement was achieved by constructing a comprehensive size field. Finally, high-quality surface and volume meshes were generated using the advancing-front technique (AFT) and Delaunay algorithms. Two human hipbones, 13 muscles, and one articular cartilage sample were modelled. The hip model was simplified and the mesh was generated using the method proposed in this study. The smallest angle of most surface mesh elements was greater than 45°, and the triangular numbers in this optimal angle interval were superior to those generated by the AFT algorithms. Eight quality evaluation parameters of the mesh model were tested using the check-elems tool. The femoral meshing results in this work were more accurate than those obtained with the AFT algorithms. The results of the vastus lateralis mesh generation were superior to the results obtained with the existing algorithm, except for the volume skew parameter. The proportions for the high-quality tetrahedral elements obtained using Wang's algorithm for the femur and the vastuslateralis muscle were 17.81% and 24.50%, respectively. The proportions obtained using the hypermesh software were 16.31% and 22.87% for the femoral and vastuslateralis models, respectively. The proposed method had better adaptability to the complex model. The generated mesh was uniform and contained smooth transitions. The mesh generation result was similar to the original geometric model, which made the assembly model fit more accurately. This was significant for the convergence of the finite-element analysis program.